Position of the Fatwa of the National Sharia Council in the Fiqh Development of Sharia Financial Institutions - Supandi, Ach Faqih; Bastomi Dani Umbara; Khittah Ashilah; Kiki Azakia (Wealth: Journal of Islamic Banking and Finance, 2025)
The purpose of the study was to further see the fatwa position of the National Sharia’ah Council in the development of Islamic economic and business fiqh in Indonesia as well as the implementation of duties and functions of the National Sharia’ah Council. Under the applicable statutory regulations, particularly Act No. 21 Year 2008 on Sharia Banking, there is a duty for regulators in this case the Bank of Indonesia to have the charge material contained in the Fatwa MUI absorbable and transformed in formulating Sharia’ah principles in the economic and financial fields of Shariaa into payload material of the Legislation Regulations which have legal and binding powers in general. Fatwa with classical definitions undergoes development and strengthening of positions in institutionalized and collective contemporary fatwa in Indonesia. Both issued by the MUI Fatwa Commission on religious and societal matters in general, as well as those issued by the DSN-MUI or fatwa on Sharia economic issues, particularly the Sharia Economic Institution. The fatwa issued by the MUI Fatwa Commission became a generally applicable referral as well as binding to the ummah of Islam in Indonesia, particularly morally. The DSN fatwa is becoming a binding reference to the existing Shariaa’ah financial institutions (LKS) in the homeland, as well as binding to communities interacting with the LKS.